DRIVING CUSTOMER SATISFACTION THROUGH PRODUCT QUALITY, SERVICE EXCELLENCE, AND EMPLOYEE PERFORMANCE: INSIGHTS FROM BSI BOGOR - Parhana, Parhana; Nawawi, Kholil; Kartika, Tika (Al-Infaq: Jurnal Ekonomi Islam, 2024)
This study aims to determine the effect of product quality and service quality and employee performance on customer satisfaction at Bank Syariah Indonesia (Case Study of BSI Customers in Bogor City). The subjects of this research are BSI customers. The data collection technique used was a questionnaire. By distributing questionnaires to 100 respondents. This sampling technique is non-probability sampling through purposive sampling technique. The research method used is multiple linear regression analysis using the SPSS version 29 software. Partially tested, the two independent variables namely product quality (X1) and employee performance (X3) have an effect on customer satisfaction with a significant level of product quality (X1) 0.014 <0.05, and employee performance (X3) 0.001 <0.05. While one independent variable, namely service quality (X2) has no significant effect on customer satisfaction with a significant level of servicequality (X2) 0.068> 0.05.